2018
DOI: 10.1002/ece3.4711
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative acoustic differentiation of cryptic species illustrated with King and Clapper rails

Abstract: Reliable species identification is vital for survey and monitoring programs. Recently, the development of digital technology for recording and analyzing vocalizations has assisted in acoustic surveying for cryptic, rare, or elusive species. However, the quantitative tools that exist for species differentiation are still being refined. Using vocalizations recorded in the course of ecological studies of a King Rail (Rallus elegans) and a Clapper Rail (Rallus crepitans) population, we assessed the accuracy and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…This paper showed that two closely related species, with an overall similar vocalization, nevertheless possess fine, but significant differences of acoustic features that may be important to transmit species-specific information and to discriminate between conspecific and heterospecific vocalizations, like found by Elfström (1992) for A. petrosus and A. pratensis . This finding is confirmed by other authors for some species of the genus Anthus (Fijen 2014; Garner et al 2015) and for bird species belonging to other taxa (Stiffler et al 2018; Tietze et al 2008). On the other hand, many bioacoustics researches found interspecific communication mediated by various bird call types (Johnson et al 2003; Goodale and Kotagama 2005; Magrath et al 2007; Templeton and Greene 2007; Magrath et al 2009; Fallow et al 2011; Fallow et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…This paper showed that two closely related species, with an overall similar vocalization, nevertheless possess fine, but significant differences of acoustic features that may be important to transmit species-specific information and to discriminate between conspecific and heterospecific vocalizations, like found by Elfström (1992) for A. petrosus and A. pratensis . This finding is confirmed by other authors for some species of the genus Anthus (Fijen 2014; Garner et al 2015) and for bird species belonging to other taxa (Stiffler et al 2018; Tietze et al 2008). On the other hand, many bioacoustics researches found interspecific communication mediated by various bird call types (Johnson et al 2003; Goodale and Kotagama 2005; Magrath et al 2007; Templeton and Greene 2007; Magrath et al 2009; Fallow et al 2011; Fallow et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The analysis provided here for the Chestnut-backed Buttonquail and the methods described provide a foundation for this application and future work on other species of button-quail. The use of acoustic detection has proven effective for other highly cryptic but vocal species (Stiffler et al 2018;Znidersic et al 2020). The Chestnut-backed Button-quail, like others of the genus, appears highly vocal at certain periods of the year, which lends itself favourably to this application.…”
Section: Drummentioning
confidence: 99%
“…; De Queiroz, 2007), providing researchers with plenty of other potential means of species identification besides morphology. Consequently, cryptic species have been differentiated by various approaches ranging from molecular genetics (Fišer et al, 2018), to proteomics (Wilke et al, 2020), to pheromones (Lassance et al, 2019), and acoustic signals (Stiffler et al, 2018), to name a few. Naturally, some methods are taxon specific whereas others have broad applicability across the tree of life, making them ideal for standardization efforts.…”
Section: Accounting For Cryptic Species In Routine Ecotoxicological S...mentioning
confidence: 99%